The role of microglia and myeloid immune cells in acute cerebral ischemia - Benakis, Corinne; Garcia-Bonilla, Lidia; Iadecola, Costantino; Anrather, Josef (Frontiers in Cellular Neuroscience, 2015)
The immune response to acute cerebral ischemia is a major contributor to stroke pathobiology. The inflammatory response is characterized by the participation of brain resident cells and peripheral leukocytes. Microglia in the brain and monocytes/neutrophils in the periphery, have a prominent role in initiating, sustaining and resolving post-ischemic inflammation. In this review we aim to summarize recent literature concerning the origins, fate and role of microglia, monocyte and neutrophil in models of cerebral ischemia and to discuss their relevance for human stroke.